Voluntary IFRS Adoption by Cameroonian World-Class Entities - Mfouapon, Georges Kriyoss; Nhiomog, William Junior; Zogning, Félix (Journal of Accounting, Business and Management (JABM), 2024)
The voluntary adoption of International Financial Reporting Standards (IFRS) is at the heart of several theoretical and empirical studies that focus on the international harmonisation of accounting practices. Despite the rise of entities with international standing in developing economies, this resounding issue has largely and regrettably been ignored in this particular context. To help fill the gap, an exploratory qualitative study was conducted with three private entities in Cameroon in an effort to understand and analyse the factors that encourage certain large entities in French-speaking Africa to comply with the IFRS when producing and reporting accounting and financial information to their stakeholders. The results obtained over time reveal that economic calculations based on expectations, along with international legitimacy and entrenchment, form the basis of early and voluntary IFRS adoption by the entities under consideration.